Wielkość i struktura finansowego wsparcia rolnictwa w Polsce i krajach członkowskich Unii Europejskiej - Kołyska, Justyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The special role of state policy on agricultural development, results from the features, characteristics and developments of agriculture as well as changes taking place in global and European agribusiness. The role of agricultural policy is still increasing and thus, expenditure on agriculture and rural areas is raising. The aim of the paper is to define the size and structure of financial support for agricultural in Poland in compared to other countries and especially European Union members, based on the indicators used by OECD. Changes in the level and structure of support for producers and consumers of agricultural products in Poland and other countries were analyzed paying attention to the effectiveness of different support instrument.